Nilai Anak dan Stimulasi Psikososial Pada Anak Laki-Laki dan Perempuan - Arlianty, Lia Shafira (FamilyEdu: Jurnal Pendidikan Kesejahteraan Keluarga, 2020)
ABSTRACTPsychosocial development is a lifetime process in every child development stage. This study aimed to analyze 1) the differences of family and children characteristics, value of child to psychosocial stimulationon betwen boys and girls children, and also to analyze 2) the corelation and influence of family and children characteristics, value of child to psychosocial stimulation. This research was using cross sectional study. One hundred was taken from families who have 2-3 years old children and live in Medan Labuhan district and Medan Area district. The results showed that no differences in mother’s age, mother and father’s education, family size, value of child and psychosocial stimulation to their boys and girls. There was a significant negative corelation between children age and value of child. There was no positive corelation between family characteristics, children characteristics, value of child and psychosocial stimulation. There was a significant positive corelation between value of child with psychosocial stimulation. Value of child have a significant positive effect on psychosocial stimulation.